Efektivitas Penggunaan Learn Social Online Platform Terhadap Kemampuan Berbicara Mahasiswa Sastra Inggris 2018 Universitas Sumatera Utara - Rahayu, Sri Dewi (JET (Journal of English Teaching), 2021)
This study focuses on the effectiveness of the Learn Social online platform on the speaking skills of English Literature 2018 students of University of Sumatera Utara. The purpose of this research is to know the Learn Social online platform is effective in improving the speaking skills of students of English Literature 2018, University of Sumatera Utara. The method used in this research is a qualitative descriptive method and the indicators used in determining the effectiveness are those proposed by Slavin (2000). The results of this study indicate that three of four indicators of the Learn Social online platform are effective on students’ speaking skills, except the indicator of instruction is not yet effective. This can be seen through the results of the questionnaires that were distributed to respondents, English Literature 2018 students, University of Sumatera Utara. Four indicators are instruction (not effective), the appropriate level of instruction (effective), incentive (effective), and time (effective).